2010
DOI: 10.4161/psb.5.10.11978
|View full text |Cite
|
Sign up to set email alerts
|

An enhancing effect of visible light and UV radiation on phenolic compounds and various antioxidants in broad bean seedlings

Abstract: Prasad and Zeeshan 10 in Plectonema boryanum and Agarwal 11 in Cassia seedlings. The UV enhancement of CAT and peroxidase (POD) activities, which are both responsible for detoxification of H 2 O 2 are probably equally important in the detoxification of H 2 O 2 , generated by SOD in Cassia seedlings. Increases in activities of peroxidases by UV radiation have been observed in several species including Cassia species 12 and potato.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…Moreover, the production of UV-B absorbing components was lower in response to UV treatment than to high light pretreatment. The same phenomenon was observed by Younis et al (2010) with overlapping antioxidant responses for high light and UV in broad bean seedlings. Bolink et al (2001) showed the reverse: growth under UV-B radiation increased photoprotection in high light situations in both pea and bean plants based on elevated thiol and UV-absorbing compound concentrations.…”
Section: Discussionsupporting
confidence: 60%
“…Moreover, the production of UV-B absorbing components was lower in response to UV treatment than to high light pretreatment. The same phenomenon was observed by Younis et al (2010) with overlapping antioxidant responses for high light and UV in broad bean seedlings. Bolink et al (2001) showed the reverse: growth under UV-B radiation increased photoprotection in high light situations in both pea and bean plants based on elevated thiol and UV-absorbing compound concentrations.…”
Section: Discussionsupporting
confidence: 60%
“…It is well‐known that the strawberries have a high content of antioxidants (anthocyanins, tannins, catechin, quercetin, kaempferol, gallic acid derivatives, vitamins C, E, and carotenoids) (Kårlund et al., ). Moreover, it has been suggested that UV‐irradiation increase the content of these antioxidant in the fruits (Alothman et al., ; Perkins, Collins, Perkins‐veazie, Collins, & Howard, ; Younis et al., ). Therefore, in the present study, we first irradiated strawberry slices with UV‐C; then, strawberry extract was prepared as described above.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments on Vicia faba, glutathion was observed as ineff ective to prevent hyperhydricity, suggesting that the response to in vitro conditions of faba bean is extremely genotype-dependent and that faba bean in general is excessively sensitive to stress conditions a er treatment with chemical substances. Use of antioxidants in faba bean tissue cultures is frequent (Abdelwahd et al, 2008;Ismail et al, 2011, Younis et al, 2010, but their apparent inconsistency is probably not due to "human errors" but rather to these factors above. The diff erences between plant species (even in the family Leguminosae) result in inconvenience to generalize such results and make recommendations for e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Initial response of plants to pathogen attack is an oxidative burst with rapid and transient production of reactive oxygen species (ROS) (Wojtaszek, 1997in Dan, 2008. In faba bean, even germination of seeds under dark conditions induce increased activity of antioxidant enzymes (Younis et al, 2010) and further, faba bean cuttings of explants lead to rapid strong phenol production, mainly on callus zones. During normal cellular metabolism plants continuously produce ROS but they also simultaneously scavenge these ROS with the help of antioxidant enzymes and/or metabolites (Watanabe et al, 2006in Younis et al, 2010.…”
mentioning
confidence: 99%
See 1 more Smart Citation